Social Values in The Novel The Hunger Games by Suzanne Collins - Faisal Ramadhani; Rahma Dewi Hartati (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2024)
This research aims to explain the social values in the novel The Hunger Games. The research method used is in the form of qualitative descriptive using content data analysis. The data of this research is in the form of words, sentences, and speech (dialogue) contained in the novel. The results of this study show that there is a social phenomenon in the story that contains competition, betrayal, and the existence of social gaps between the characters, but in this story there are also social values that can be learned, namely: 1) the value of affection consisting of loyalty, help, and care, 2) the value of responsibility in the form of the value of empathy and mutual ownership, 3) the value of life harmony in the form of cooperation.